The integration of corporate social responsibility into the digital transformation of the sports industry - Skorokhodov S.N. ,; Abdybekova N.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to comprehensive examination of the aspects that contribute to the sustainable digital advancement of the sports sector, with a particular focus on social and corporate accountability. Methods and structure of the study. In the course of our research, we employed a variety of approaches, including system analysis, comparative analysis, classification, and a structural and functional approach. Results and conclusions. The findings of the research led to a logical and scientifically sound conclusion: the success and effectiveness of the digital transformation in the sports sector is directly linked to the level of integration of corporate and social responsibility into the marketing and management strategies of both commercial and public organizations. The innovative and investment appeal of the sports sector is fostered and enhanced through the systematic development of customer-centric models of engagement with the target audience, which encompass both the elements of digital transformation and the holistic incorporation of corporate and social responsibility.